Conceptual principles of fencing development in children’s sports schools in Ukraine - Driukov, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to work out conceptual principles for successful and dynamic development of fencing in children’s sports schools in Ukraine. Material: the researches were conducted on material of children’s sports school Dynamo in Kiev. In this work we used SWOT analysis - method of strategic planning, which implies determination of external and internal factors of organization and their dividing into four categories: strengths (strong sides), weaknesses (weak sides), opportunities and threats. For determination of experts’ opinion concordance in SWOT analysis we used concordance coefficient. Results: we worked out conception of fencing development in children’s sports schools in Ukraine in modern conditions. The specificity of this conception implies determination of strategic approaches to further fencing progressing in children’s sports schools in Ukraine. The conception can serve as bench mark for development and realization of program documents in sphere of fencing progressing or its different branches. Conclusions: we have worked out conception of fencing progressing in children’s sports schools in Ukraine, which is based on achievements and traditions of fencing in Ukraine and in the world. Its development is based on systemic analysis of internal and external factors, which influence on development of fencing in sports schools and on choice of its progressing strategy in new social economical conditions.